The Impact of IgA and the Microbiota on CNS Disease - Pu, Annie; Lee, Dennis S. W.; Isho, Baweleta; Naouar, Ikbel; Gommerman, Jennifer L. (Frontiers in Immunology, 2021)
Although anatomically distant from the central nervous system (CNS), gut-derived signals can dynamically regulate both peripheral immune cells and CNS-resident glial cells to modulate disease. Recent discoveries of specific microbial taxa and microbial derived metabolites that modulate neuroinflammation and neurodegeneration have provided mechanistic insight into how the gut may modulate the CNS. Furthermore, the participation of the gut in regulation of peripheral and CNS immune activity introduces a potential therapeutic target. This review addresses emerging literature on how the microbiome can affect glia and circulating lymphocytes in preclinical models of human CNS disease. Critically, this review also discusses how the host may in turn influence the microbiome, and how this may impact CNS homeostasis and disease, potentially through the production of IgA.